Combination of Ablation and Immunotherapy for Hepatocellular Carcinoma: Where We Are and Where to Go - Wang, Kunpeng; Wang, Cong; Jiang, Hao; Zhang, Yaqiong; Lin, Weidong; Mo, Jinggang; Jin, Chong (Frontiers in Immunology, 2021)
Hepatocellular carcinoma (HCC) is the third leading cause of cancer-related deaths worldwide and is increasing in incidence. Local ablative therapy plays a leading role in HCC treatment. Radiofrequency (RFA) is one of the first-line therapies for early local ablation. Other local ablation techniques (e.g., microwave ablation, cryoablation, irreversible electroporation, phototherapy.) have been extensively explored in clinical trials or cell/animal studies but have not yet been established as a standard treatment or applied clinically. On the one hand, single treatment may not meet the needs. On the other hand, ablative therapy can stimulate local and systemic immune effects. The combination strategy of immunotherapy and ablation is reasonable. In this review, we briefly summarized the current status and progress of ablation and immunotherapy for HCC. The immune effects of local ablation and the strategies of combination therapy, especially synergistic strategies based on biomedical materials, were discussed. This review is hoped to provide references for future researches on ablative immunotherapy to arrive to a promising new era of HCC treatment.